Effects of β-glucan and Vitamin D Supplementation on Inflammatory Parameters in Patients with Diabetic Retinopathy - Richter, Josef; Závorková, Martina; Vetvicka, Vaclav; Liehneová, Ivana; Kral, Vlastimil; Rajnohova Dobiasova, Lucie (Journal of dietary supplements, 2019)
The objective of this article is to evaluate the potential effects of beta-glucan and vitamin D supplementation in patients with diabetic retinopathy. We evaluated the levels of several parameters of inflammatory reactions (C-reactive protein [CRP], serum amyloid A [SAA], and interleukin- [IL-] 6), leptin, and vitamin D. Using a 3-month interval, we divided the patients into three groups: (1) supplemented with beta-glucan and vitamin D, (2) supplemented with vitamin D and placebo, and (3) supplemented with vitamin D alone. By this division, we aim not only to observe whether beta-glucan can increase the effects of vitamin D, but also to eliminate the potential effects of placebo. The doses of vitamin D corresponded to phototype, weight, age, and sex of the individual. Fifty-two diabetic retinopathy patients were selected for our study. We found significant vitamin D deficits in all cases, even after three months of supplementation with vitamin D. Significant changes in levels of CRP were observed in the beta-glucan-supplemented group; levels of SAA and IL-6 were not changed. Leptin levels were significantly lowered in the beta-glucan-supplemented group and increased in the other groups. More detailed studies and/or longer supplementation is necessary.
Keywords: zánět; Female; placebo; diabetická retinopatie; C-Reactive Protein; beta-glukany; ženské pohlaví; sérový amyloid A; Leptin; lidé; beta-glucan; vitamin D; nedostatek vitaminu D; Interleukin-6; Aged, 80 and over; CRP; Vitamin D; Inflammation; leptin; Diabetic Retinopathy; Male; Aged; Czech Republic; beta-Glucans; Serum Amyloid A Protein; index tělesné hmotnosti; interleukin-6; Placebos; Vitamin D Deficiency; Česká republika; lidé středního věku; C-reaktivní protein; senioři nad 80 let; senioři; mužské pohlaví; Body Mass Index; Middle Aged; IL-6; Humans